The subjective experience of transcranial electrical stimulation: a within-subject comparison of tolerability and side effects between tDCS, tACS, and otDCS - Bjekić, Jovana; Živanović, Marko; Stanković, Marija; Paunović, Dunja; Konstantinović, Uroš; Filipović, Saša R. (Frontiers in human neuroscience, 2024)
Low-intensity transcranial electrical stimulation (tES), including techniques like transcranial direct current stimulation (tDCS), transcranial alternating current stimulation (tACS), and oscillatory transcranial direct current stimulation (otDCS), has been widely explored for its neuromodulatory effects on motor, cognitive, and behavioral processes. Despite well-established safety, these techniques can induce varying degrees of discomfort and side effects, potentially impacting their application. This study presents a within-subject sham-controlled experiment directly comparing the subjective experience and side effects of tDCS, tACS, and otDCS. Participants reported their discomfort levels at multiple time points during 20-min stimulation sessions and completed a side-effects questionnaire before and after each session. Results indicated that the overall discomfort levels were low across all conditions, with ≥95% reporting the absence of discomfort or mild procedure-induced discomfort. Nevertheless, tDCS and otDCS were slightly less comfortable compared to sham, especially at the beginning of stimulation, with tACS-induced discomfort levels being overall comparable to sham. The most common side / adverse effects were mild skin sensations, including itching and tingling, particularly with tDCS and otDCS, while tACS occasionally caused phosphenes and blurred vision. These findings provide a systematic comparison of tES-induced discomfort and side effects between different tES techniques, highlighting the high safety of tES, but also the importance of considering within- and between-person variability and time-course effects in tES applications.